Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Removal of fluoroquinolone antibiotic from wastewater based on immobilized metal affinity mechanism - L Zhao; B. Jia; M. He; H. Hu; Y. Guo; G. Fu; C. Hou; S. Gao; R. Li; X. Lv (International Journal of Environmental Science and Technology, 2025)

Mapping the landscape of bird strike research: insights from a quantitative analysis - H. X. Wang; W. Fu; N. A. Razak; Y. Y. Shi (International Journal of Environmental Science and Technology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P10-08 Evaluation of real-life PFAS mixture toxicity and impact on 3D placenta spheroid model - Y. Xia; Q. Fu; H. Voss; S. Fest; A.C. Zenclussen; V. Stojanovska (Toxicology Letters, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Genetics and metabolic responses of Artemisia annua L to the lake of phosphorus under the sparingly soluble phosphorus fertilizer: evidence from transcriptomics analysis - Lingyun Wan; Juan Huo; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Mohamed A. Abd Elhamid; Salma A. Soaud; Rania M. Y. Heakel; Jihai Gao; et al. (Functional & Integrative Genomics, 2024)

16s-RNA sequencing analysis of the influence of UV radiation on the metabolic pathways of pollutants in the A2O process - Y. W. Li; J. H. You; Y. C. Zong; J. Wang; C. H. Fu (International Journal of Environmental Science and Technology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Petrogenesis and tectonic implications of the early Paleozoic granites in the Lincang granitic batholith, southwestern China: Constraints from geochronology, geochemistry and Hf isotopes - Qian R. Xiao; Qiang Wang; Zhong Y. Liu; Fu H. Xiong; Lei Fan; Han Zhao; Ting T. Gong (Ore and Energy Resource Geology, 2023)

Cymbopogom Citratus Essential Oils: A Promising Source of Antifungals Against Panax Notoginseng-Associated Pathogenic Fungi - Jing Yang; Tian T. Li; Ying Y. Huo; Heng Y. Huang; Qing H. Meng; Fu R. Xu; Xian Dong (Current Microbiology, 2023)

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

Effects of environmental factors on release amount of heavy metal and structure of microbial community in sediments - T. Wen; H. Zhong; G. Fu; Y. Zhong (International Journal of Environmental Science and Technology, 2022)

Characteristics and formation mechanisms of Mesozoic compressional structures in the Huanghua Depression, Bohai Bay Basin, China - W. Li; F. Zhang; Y. Zhang; L. Fu; H. Li (Australian Journal of Earth Sciences, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Specific genes and sequence variation in pathotype 7 of the clubroot pathogen Plasmodiophora brassicae - H. Yang; J. Zheng; Y. D. Fu; Y. H. Zhang; C. L. Yi; C. Jin; Y. Huang; Wenming Wang (European Journal of Plant Pathology, 2020)

Characteristics changes in banana peel coagulant during storage process - Y. Fu; X. J. Meng; N. N. Lu; H. L. Jian; Y. Di (International Journal of Environmental Science and Technology, 2019)

Evaluation of Stripe Rust Resistance in Hungarian Winter Wheat Cultivars in China - D. Huang; H. Zhang; M. Tar; Y. Zhang; F. Ni; J. Ren; D. Fu; L. Purnhauser; J. Wu (Cereal Research Communications, 2019)

Sequence stratigraphy and Quaternary depositional systems in the Sanhu area of the Qaidam Basin, northwest China - Z. Liu; S. Fu; H. C. Jia; J. X. Tian; Y. H. Chen; C. Y. Dong (Australian Journal of Earth Sciences, 2019)

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Reservoir characteristics and methane adsorption capacity of the Upper Triassic continental shale in Western Sichuan Depression, China - Y. C. Liu; D. X. Chen; N. S. Qiu; Y. Wang; J. Fu; Y. Huyan; J. K. Jia; H. Wu (Australian Journal of Earth Sciences, 2017)

A GCM investigation of impact of aerosols on the precipitation in Amazon during the dry to wet transition - Yu Gu; K. N. Liou; J. H. Jiang; R. Fu; Sarah Lu; Y. Xue (Climate Dynamics, 2017)

Colored Sticky Traps to Selectively Survey Thrips in Cowpea Ecosystem - L D Tang; H Y Zhao; B L Fu; Y Han; K Liu; J H Wu (Neotropical Entomology, 2016)

Development of roughness updating based on artificial neural network in a river hydraulic model for flash flood forecasting - J C Fu; M H Hsu; Y Duann (Journal of Earth System Science, 2016)

Meta-analyses of structural regional cerebral effects in type 1 and type 2 diabetes - Calum D. Moulton; Sergi G. Costafreda; Paul Horton; Khalida Ismail; Cynthia H. Y. Fu (Brain Imaging and Behavior, 2015)

Effect of the invasive bivalve Mytilopsis sallei on the macrofaunal fouling community and the environment of Yundang Lagoon, Xiamen, China - L.-Z. Cai; J.-S. Hwang; H.-U. Dahms; S.-J. Fu; Y. Zhuo; T. Guo (Hydrobiologia, 2014)

Quantitative trait analysis of flowering time in spring rapeseed (B. napus L.) - Y. X. Luo; C. Y. Luo; D. Z. Du; Z. Fu; Y. M. Yao; C. C. Xu; H. S. Zhang (Euphytica, 2014)

Oncogenic and tumor suppressive roles of microRNAs in apoptosis and autophagy - Y. Chen; L. L. Fu; X. Wen; B. Liu; J. Huang; J. H. Wang; Y. Q. Wei (Apoptosis, 2014)

Prevalence of carbapenem-hydrolyzing class D β-lactamase genes in Acinetobacter spp. isolates in China - S. Ji; Y. Chen; Z. Ruan; Y. Fu; J. Ji; Y. Fu; H. Wang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Study on elastic P-wave propagation law in unfavorable geologic structures with discontinuous deformation analysis method - Y. H. Zhang; X. D. Fu; Q. Sheng; X. L. Leng (Arabian Journal of Geosciences, 2013)

A Factorial-based Dynamic Analysis Method for Reservoir Operation Under Fuzzy-stochastic Uncertainties - D. Z. Fu; Y. P. Li; G. H. Huang (Water Resources Management, 2013)

Scanning Electron Microscopy Studies of the Antennal Sensilla of Metaphycus parasaissetiae Zhang & Huang (Hymenoptera: Encyrtidae) - H Zhou; W J Wu; F P Zhang; Y G Fu (Neotropical Entomology, 2013)

Scl gene construction, expression and effect on hemangioma - H. X. Yin; Z. H. Zhang; J. C. Shen; A. L. Zhang; T. Y. Zhang; J. X. Luo; C. Y. Fu; X. P. Yi; Z. W. Liu; S. S. Yang; B. Zhou; X. Fu (Molecular Biology Reports, 2013)

Arsenic accumulation and distribution in the tissues of inbred lines in maize (Zea mays L.) - Z. H. Liu; W. H. Li; H. Y. Qi; G. L. Song; D. Ding; Z. Y. Fu; J. B. Liu; J. H. Tang (Genetic Resources and Crop Evolution, 2012)

Hydrocarbon- and ore-bearing basinal fluids: a possible link between gold mineralization and hydrocarbon accumulation in the Youjiang basin, South China - X. X. Gu; Y. M. Zhang; B. H. Li; S. Y. Dong; C. J. Xue; S. H. Fu (Mineralium Deposita, 2012)

Correlation between plasma amino acid profiles and the various stages of hepatitis B infection - J. Yang; J. He; H. Cao; X. Zhao; S. Fu; H. Lu; Y. Chen; X. Pan; L. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Constitutive expression of barley α-amylase in Pichia pastoris by high-density cell culture - Z. W. Liu; H. X. Yin; X. P. Yi; A. L. Zhang; J. X. Luo; T. Y. Zhang; C. Y. Fu; Z. H. Zhang; J. C. Shen; L. P. Chen (Molecular Biology Reports, 2012)

A fuzzy-Markov-chain-based analysis method for reservoir operation - D. Z. Fu; Y. P. Li; G. H. Huang (Stochastic Environmental Research and Risk Assessment, 2012)

Molecular cloning, characterization and expression analysis of B cell translocation gene 1 in grass carp Ctenopharyngodon idella - Y. J. Fu; F. G. Huang; T. Yuan; J. R. Gu; G. Q. Luo; H. Xu (Journal of Fish Biology, 2012)
An expressed sequence tag (EST) of B cell translocation gene (BTG) 1 ( gcbtg1 ) was obtained from a grass carp Ctenopharyngodon idellus intestinal complementary (c)DNA library and the full‐length cDNA sequence was acquired by rapid amplification of cDNA ends (RACE) technology. The predicted Gcbtg1 protein contains the box A and box B motifs which characterized the BTG and transducer of ERBB2 (TOB) family. Multiple alignment analysis reveals that Gcbtg1 shares an overall identity of 65–94% with Gcbtg1s of other vertebrates. Real‐time quantitative PCR analysis reveals that the highest expression level of gcbtg1 was detected in liver and the lowest in muscle. Western blotting analysis indicates that the immunological cross‐reactivity occurs between C. idella and human Homo sapiens BTG1 protein. A 1008 bp 5′‐flanking region sequence was cloned and analysed.

A new long terminal repeat (LTR) sequence allows to identify J genome from JS and St genomes of Thinopyrum intermedium - Z. X. Tang; Z. J. Yang; S. L. Fu; M. Y. Yang; G. R. Li; H. Q. Zhang; F. Q. Tan; Zhenglong Ren (Journal of Applied Genetics, 2011)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

QTL detection for grain oil and starch content and their associations in two connected F2:3 populations in high-oil maize - Y. Z. Wang; J. Z. Li; Y. L. Li; M. G. Wei; X. H. Li; J. F. Fu (Euphytica, 2010)

Comparison of approaches for efficient gene silencing induced by microRNA-based short hairpin RNA and indicator gene expression - Z. X. Shan; Q. X. Lin; C. Y. Deng; Z. L. Zhou; H. H. Tan; Y. H. Fu; X. H. Li; J. N. Zhu; L. P. Mai; S. J. Kuang; S. G. Lin; X. Y. Yu (Molecular Biology Reports, 2010)

Vertical Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Soil Cores Taken from a Typical Electronic Waste Polluted Area in South China - Z. Z. Yang; Y. F. Li; Y. X. Hou; H. Y. Liang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Tissue Distribution of Polybrominated Diphenyl Ethers (PBDEs) in Captive Domestic Pigs, Sus scrofa, from a Village Near an Electronic Waste Recycling Site in South China - Y. F. Li; Z. Z. Yang; C. H. Wang; Z. J. Yang; Z. F. Qin; S. Fu (Bulletin of Environmental Contamination and Toxicology, 2010)

Dent corn genetic background influences QTL detection for grain yield and yield components in high-oil maize - Y. L. Li; X. H. Li; J. Z. Li; J. F. Fu; Y. Z. Wang; M. G. Wei (Euphytica, 2009)

Composition, Distribution, and Characterization of Polycyclic Aromatic Hydrocarbons in Soil in Linfen, China - S. Fu; H. X. Cheng; Y. H. Liu; X. J. Xia; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Organochlorine Pesticides in the Soil in Linfen, China - H. X. Cheng; S. Fu; Y. H. Liu; D. S. Li; J. H. Zhou; X. J. Xia (Bulletin of Environmental Contamination and Toxicology, 2008)

Polychlorinated Biphenyls Residues in the Soil in Linfen, China - S. Fu; H. Cheng; Y. Liu; L. Zhang; Z. Yang; K. Li; X. Xia; X. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Two new flavanes and bioactive compounds from Daphne tangutica Maxim - W. Zhang; Y. H. Shen; Z. Y. Lou; R. H. Liu; C. Zhang; P. Fu; L. Shan; W. D. Zhang (Natural Product Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular characterization of the surface glycoprotein genes of an H5N1 influenza virus isolated from a human in Guangdong, China - J.-J. Zhou; J. Fu; D.-Y. Fang; H.-J. Yan; J. Tian; J.-M. Zhou; J.-P. Tao; Y. Liang; L.-F. Jiang (Archives of Virology, 2007)

Modulation of neural response to happy and sad faces by acute tryptophan depletion - Paolo Fusar-Poli; Paul Allen; Francis Lee; Simon Surguladze; Nigel Tunstall; Cynthia H. Y. Fu; Michael J. Brammer; Anthony J. Cleare; Philip K. McGuire (Psychopharmacology, 2007)

Sesquiterpene lactones from Saussurea alata - G. Ren; Z. M. Yu; Y. L. Chen; S. H. Wu; C. X. Fu (Natural Product Research, 2007)

Octad pollen formation in Cymbopetalum (Annonaceae): the binding mechanism - C. -H. Tsou; Y. -L. Fu (Plant Systematics and Evolution, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Two new xanthones from Hypericum japonicum - P. Fu; W.-D. Zhang; R. H. Liu; T.-Z. Li; Y.-H. Shen; H.-L. Li; W. Zhang; H.-S. Chen (Natural Product Research, 2006)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Effect of acute tryptophan depletion on pre-frontal engagement - Paul P. Allen; Anthony J. Cleare; Francis Lee; Paolo Fusar-Poli; Nigel Tunstall; Cynthia H. Y. Fu; Micheal J. Brammer; Philip K. McGuire (Psychopharmacology, 2006)

Genetic analyses and mapping of a new thermo-sensitive genic male sterile gene in maize - J. H. Tang; Z. Y. Fu; Y. M. Hu; J. S. Li; L. L. Sun; H. Q. Ji (Theoretical and Applied Genetics, 2006)

Seasonal Variation of the Particle Size Distribution of n-Alkanes and Polycyclic Aromatic Hydrocarbons (PAHs) in Urban Aerosol of Guangzhou, China - X. L. Tang; X. H. Bi; G. Y. Sheng; J. H. Tan; J. M. FU (Environmental Monitoring and Assessment, 2006)

QTLs for drought escape and tolerance identified in a set of random introgression lines of rice - J. L. Xu; H. R. Lafitte; Y. M. Gao; B. Y. Fu; R. Torres; Z. K. Li (Theoretical and Applied Genetics, 2005)

Effects of ketamine on prefrontal and striatal regions in an overt verbal fluency task: a functional magnetic resonance imaging study - Cynthia H. Y. Fu; Kathryn M. Abel; Matthew P. G. Allin; David Gasston; Sergi G. Costafreda; John Suckling; Steve C. R. Williams; Philip K. McGuire (Psychopharmacology, 2005)

Tryptophan depletion reduces right inferior prefrontal activation during response inhibition in fast, event-related fMRI - Katya Rubia; Francis Lee; Anthony J. Cleare; Nigel Tunstall; Cynthia H. Y. Fu; Michael Brammer; Phillip McGuire (Psychopharmacology, 2005)

Simulation Studies of High-Latitude Magnetospheric Boundary Dynamics - Q. Q. Shi; Z. Y. Pu; H. Zhang; S. Y. Fu; C. J. Xiao; Q. -G. Zong; T. A. Fritz; Z. X. Liu (Surveys in Geophysics, 2005)

Energetic Particles Observed in the CUSP Region During a Storm Recovery Phase - S. Y. Fu; Q. G. Zong; Z. Y. Pu; C. J. Xiao; A. Korth; P. Daly; H. Reme (Surveys in Geophysics, 2005)

Multiple Flux Rope Events at the High-Latitude Magnetopause: Cluster/Rapid Observation on 26 January, 2001 - Z. Y. Pu; Q. -G. Zong; T. A. Fritz; C. J. Xiao; Z. Y. Huang; S. Y. Fu; Q. Q. Shi; M. W. Dunlop; K. -H. Glassmeier; A. Balogh; P. Daly; H. Reme; et al. (Surveys in Geophysics, 2005)

Molecular diversity and multilocus organization of the parental lines used in the International Rice Molecular Breeding Program - S. B. Yu; W. J. Xu; C. H. M. Vijayakumar; J. Ali; B. Y. Fu; J. L. Xu; Y. Z. Jiang; R. Marghirang; J. Domingo; C. Aquino; S. S. Virmani; Z. K. Li (Theoretical and Applied Genetics, 2003)

Distribution of Organochlorine Pesticides in a Sediment Profile of the Pearl River Estuary - X. D. Li; B. X. Mai; G. Zhang; G. Y. Sheng; J. M. Fu; S. M. Pan; O. W. H. Wai; Y. S. Li (Bulletin of Environmental Contamination and Toxicology, 2001)

Attenuated Lapinized Chinese Strain of Classical Swine Fever Virus: Complete Nucleotide Sequence and Character of 3′-Noncoding Region - H. X. Wu; J. F. Wang; C. Y. Zhang; L. Z. Fu; Z. S. Pan; N. Wang; P. W. Zhang; W. G. Zhao (Virus Genes, 2001)

CDK inhibitors suppress apoptosis induced by chemicals and by excessive expression of a cell death gene, reaper, in Drosophila cells - M. Nagano; K. Ui-Tei; H. Suzuki; Zheng-fu Piao; Y. Miyata (Apoptosis, 2000)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Genetic susceptibility to pre-eclampsia and chromosome 7q36 - G. Guo; J.A. Lade; A.N. Wilton; E.K. Moses; M. Grehan; Y. Fu; H. Qiu; D.W. Cooper; S.P. Brennecke (Human Genetics, 1999)

Studies on somaclonal variation in Phalaenopsis - W. H. Chen; T. M. Chen; Y. M. Fu; R. M. Hsieh; W. S. Chen (Plant Cell Reports, 1998)

Angiotensin II receptors: Localization of type I and type II in rat epididymides of different developmental stages - P. S. Leung; H. C. Chan; L. X. M. Fu; P. Y. Leung; S. B. C. Chew; P. Y. D. Wong (The Journal of Membrane Biology, 1997)

Comparative Analyses of Soil Contaminant Levels and Plant Species Diversity at Developing and Disused Oil Well Sites in Qianjiang Oilfield, China - Z.-T. Xiong; H.-X. Hu; Y.-X. Wang; G.-H. Fu; Z.-Q. Tan; G.-A. Yan (Bulletin of Environmental Contamination and Toxicology, 1997)

Determination of thein situ forces and force distribution within the human anterior cruciate ligament - Glen A. Livesay; Hiromichi Fujie; Shinji Kashiwaguchi; Duane A. Morrow; Freddie H. Fu; Savio L. -Y. Woo (Annals of Biomedical Engineering, 1995)